In vitro and in vivo biodegradation and biocompatibility assessment of magnesium composites for bone implants - Gmitro, Samantha; Larraza, Andres; Sotoudehbagha, Pedram; Alayon Mata, Andres; Romero, Andrew; Lovejoy, John; Razavi, Mehdi (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionWith an average of 6.8 million fractures per year in the United States, the current method for surgical intervention involves bioinert materials that do not promote osteogenesis and can have inflammatory reactions that hinder bone healing. Magnesium has emerged in research due to the material’s biodegradability and biocompatibility; however, it has a low corrosion resistance, which can lead to hydrogen gas evolution and tissue necrosis. Therefore, magnesium is typically alloyed with rare earth elements (REEs) to increase corrosion resistance. The main goal of this study involves fabricating a magnesium (Mg)‐based metal matrix nanocomposite (MMNC) containing scandium (Sc) and strontium (Sr) as alloying elements, as well as diopside (CaMgSi2O6) ‐based bioactive glass‐ceramic nanoparticles for reinforcement.MethodsMMNCs were processed using ultrasonic melt processing and hot rolling to disperse nanoparticles and refine their microstructure. These MMNCs have undergone detailed tests to determine microstructure and degradation properties, followed by in vitro and in vivo tests to determine the MMNC’s biodegradation and biocompatibility characteristics.ResultsThrough cell culture with human bone marrow-derived mesenchymal stem cells (hBM-MSCs) we determined that MMNCs provide in vitro cytocompatibility of >80%. Next, MMNC pins were implanted into rat femoral defects and monitored for 3 months post-implantation with the WE43 Mg alloy used as a control. Utilizing in vivo and ex vivo X-ray imaging and histology of these defects implanted with MMNC or WE43 pins, we found that our composite allows for no or minimal hydrogen gas evolution and fibrotic body response with osteointegration and new bone formation.DiscussionThis allows for an understanding of potential applications of our composite as a biomaterial.